KARAKTERISTIK BIODIESEL HASIL TRANSESTERIFIKASI MINYAK JELANTAH MENGGUNAKAN TEKNIK KAVITASI HIDRODINAMIK - Satriana Satriana; Nida El Husna; Desrina Desrina; Muhammad Dani Supardan (Agricultural Faculty, 2012)
This study undertakes the transesterification process of used cooking oils that have undergone a process of esterification. The transesterification process carried out by reacting methanol and esterified used cooking oil using KOH as catalyst. Stirring technique used is based on hydrodynamic cavitation. This research aims to study the characteristics of biodiesel that made from transesterified used cooking oil with different concentrations of methanol. The concentration of methanol used consists of 5 (five) level are: 99.9%, 95%, 90%, 80%, and 70%. The transesterification process using hydrodynamic cavitation technique with a 99.9% concentration of methanol result in biodiesel with characteristics consistent by Indonesian National Standard (SNI). In this condition, biodiesel produced 92.93% of the yield which has characteristics of acid number 0.80 mg KOH / g, total glycerol 0.045%, alkyl ester 99.45%, iodine number 14.92 g I2/100 g, viscosity 2,35 mm2 / s , density 0.87745 g/cm3 and pH value 4.885. Based on research, the concentration of methanol lower than 99.9% not yet can produce biodiesel from used cooking oil that have characteristics according to Indonesian National Standard (SNI).